(3hGSWg GdSdhc aj SjGSI Gdedhcs - (3ehSi Hf jhSa Hf YHO GdQMef Hf jMji Hf jYeQ GdYHOhGOi,J (B791 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd fYeJg Ydi GdNdb CeG HYO aEfg deG cGfJ GdChdGO bWY GdCcHGO hYeGO GdXghQ s
(3BNQgG (B:s
(3GPG cfJ GYde YdekG jbjfkG HCf LejY MjGJi SGYI aGYed jG Hfi HhUjJi JSYO hGMaXgG JQTO s
(3HgG fXGe GdJYbjHIs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B331s
Keywords: (3GdSjGSI hGdGLJeGYs